Malnutrition in Community-Dwelling Anorexia Nervosa Patients: Alterations of Physical and Laboratory Features - Gentile, Maria Gabriella; Manna, Giulia Maria; Iaccarino, Laura; Cometto, Luisa; Mariani, Nicoletta; Lessa, Chiara (Journal of Nutritional Therapeutics, 2012)
Background and aims: Malnutrition in Anorexia Nervosa may determine many abnormalities and consequences for both physical and psychological points. Their early detection and management may improve the prognosis. This study aims at identifying clinical predictors of disease highlight possible correlations between signs-symptoms and degree of malnutrition. Methods: The authors present a retrospective study of 302 Anorexia Nervosa outpatients aged 23.2 ± 9.4 years (`X ± SD) observed at arrival in Eating Disorder Unit. Results: 302 patients were examined, (BMI 14.7 ± 1.9 kg/m2). We observed a significant reduction of measured basal metabolic rate (less 19.3 ± 15.3%) in almost all patients, and almost one patient over four have some clinical complications such as bradycardia, hypotension, anemia, hypoglycemia, showing a high correlation with malnutrition degree. Conclusions: Determining malnutrition degree is relevant to identify and to treat Anorexia Nervosa patients as well as to contract setting of care with patients and parents for reducing delayed treatment.